Idiopathic opsoclonus myoclonus ataxia syndrome: Apresentação de um paciente pediátrico - Suclla Velásquez, Lutgarda Laura (2023)
Objective. Report a case of opsoclonus-myoclonus-ataxic syndrome or Kirnsbourne syndrome, due to its infrequent presentation, with an estimated incidence of around 1/5 000 000, 50 % or more of paraneoplastic etiology and a very limited number not described in the literature on idiopathic etiology, in addition to the fact that 70 to 80 % of patients suffering from said syndrome present subsequent neurological sequelae. Clinical case summary. We present the case of a 7-year-old girl with ataxia, myoclonus and opsoclonus of idiopathic origin, who received treatment with pulsed methylprednisolone and immunoglobulin, followed by the use of oral corticosteroids for the following months. Finally, she presented an almost complete recovery two months after starting the treatment. Conclusions. Opsoclono-myoclono-ataxic syndrome is a rare neurological disorder in pediatrics in which the presence of associated tumors must first be ruled out, among them the most important neuroblastoma and take into account that although it can be limited to only 4 months of time of disease, the mainstay of its treatment is the use of high doses of corticosteroids to prevent it from worsening as well as the appearance of possible neurological sequelae in the future.